Linguistic patterns-based translation for natural language interface - Mohd Sharef, Nurfadhlina; Mohd Noah, Shahrul Azman (IEEE (IEEE Xplore), 2014)
Semantic technology improves classical information retrieval by representing the information in a structured form and with notion of understanding. The querying process however requires formal language which could be challenging to novice users. The natural language interface research addresses this issue by translating the user's question into the formal query. Existing studies have provided limited question understanding coverage due to limitation on single triple translation only. This paper addresses deeper understanding of semantic natural language through twelve linguistic patterns. The result has shown that the method manages to extract the linguistic expressions and aid the translation process. This concludes that wider linguistic coverage can be provided by higher linguistic expressions processing.